Makna dan Peran Customer Relationship Management (CRM) dalam Membangun Loyalitas Pelanggan Sebuah Studi Kualitatif - Muhammad Salka Falwaguna; Elvira Firdayanti; Hersa Ridwan Firdaus; Yani Iriani (Pusat Riset dan Inovasi Nasional, 2026)
In the digital era characterized by intense business competition, Customer Relationship Management (CRM) has evolved from a transactional approach to a relational strategy that emphasizes building customer trust and loyalty through personalized experiences. This qualitative study employed a literature review approach to examine the meaning and role of CRM in fostering customer loyalty within Indonesia's service sector. The study population consisted of credible publications published between 2021 and 2025 and indexed in Scopus and Google Scholar. A purposive sampling technique was applied to select more than 20 peer-reviewed sources. The research instruments included a structured literature search protocol and a thematic analysis matrix, while the data were analyzed using descriptive qualitative synthesis supported by triangulation. The findings indicate that CRM functions as a holistic relational philosophy that enhances customer loyalty through personalization (90%), effective data management (88%), and superior customer experience (95%). CRM implementation has proven effective across various service industries, including banking, retail, hospitality, e-commerce, telecommunications, and the automotive sector. Critical success factors include strong management commitment and a customer-centric organizational culture. The study concludes that the integration of CRM contributes to sustainable business profitability. Future research is recommended to incorporate primary data from micro, small, and medium-sized enterprises (MSMEs) to provide more comprehensive empirical evidence.